BEST PRACTICE PENINGKATAN PRESTASI BELAJAR SENI BUDAYA MELALUI PEMBELAJARAN EXPERIENTIAL LEARNING KELAS X TKJ SMK NEGERI 3 BALIKPAPAN - MUHAMMAD YUSRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This Best Practice is the author's best experience in learning Cultural Arts. The background of this best practice problem is the existence of problems in the form of student complaints that students are sometimes lazy to create Decorative Arts in the form of exploration of Decorative patterns in the form of Static or Dynamic. This is the cause for students when they take Cultural Arts lessons, so students only learn to draw as they are. Based on this problem, the author tries to apply Cultural Arts learning which is the assignment of an Exhibition at the end of the Semester, which will be held in June 2020. The purpose of this best practice is to find out whether students are enthusiastic about participating in Cultural Arts lessons in the assignment of Ornamental Art Exhibition based on Dayak motifs. The formulation of the problem is whether the task of the Dayak Motif-based Ornamental Art Exhibition in class X can increase their enthusiasm in participating in Cultural Arts learning. The results obtained by applying Cultural Arts learning in the form of an exhibition of Decorative Arts works based on Dayak motifs in class X turned out to be very active and enthusiastic in participating in the exhibition which was held for 3 days. This is evident from the results of learning Arts and Culture in the form of enthusiastic exhibition assignments, and reaching a percentage of 82.86%, far from the standard level of completeness set by the school which is only 75%. The conclusion of this best practice is that the Cultural Arts learning model in the form of Exhibition assignments is proven to be able to improve student achievement in Cultural Arts Lessons for class X SMKN 3 Balikpapan. ABSTRAKBest Practice ini merupakan pengalaman terbaik penulis dalam pembelajaran Seni Budaya. Latar belakang masalah best practice ini adalah adanya permasalahan berupa keluhan siswa bahwa siswa terkadang malas berkarya Seni Ragam Hias dalam bentuk eksplorasi pola Hias yang berbentuk Statis maupun Dinamis. Hal ini menjadi penyebab pada siswa saat mengikuti pelajaran Seni Budaya, sehingga siswa hanya belajar cenderung menggambar apa adanya. Berdasarkan masalah ini penulis mencoba menerapkan pembelajaran Seni Budaya yang bersifat pemberian tugas Pameran pada akhir Semester, yang dilaksanakan di bulan Juni 2020. Tujuan best practice ini adalah untuk mengetahui apakah siswa antusias mengikuti pelajaran Seni Budaya pada pemberian tugas Pameran Seni Rgam Hias berbasis motif Dayak. Rumusan masalah adalah apakah tugas Pameran Seni Ragam Hias berbasis Motif Dayak pada kelas X dapat meningkatkan antusiasnya dalam mengikuti pembelajaran Seni Budaya. Hasil yang diperoleh dengan menerapkan pembelajaran Seni Budaya dalam bentuk tugas Pameran karya Seni Ragam Hias yang berbasis motif Dayak pada kelas X ternyata siswa sangat aktif dan antusias mengikuti Pameran tersebut yang dilaksanakan selama 3 hari. Hal ini terbukti dari hasil pembelajaran Seni Budaya dalam bentuk tugas Pameran yang antusias tersebut, dan mencapai prosentase 82,86% jauh dari tingkat standar ketuntasan yang ditetapkan oleh sekolah yang hanya 75%. Kesimpulan dari best practice ini adalah bahwa model pembelajaran Seni Budaya dalam bentuk tugas Pameran terbukti dapat meningkatkan prestasi belajar siswa pada Pelajaran Seni Budaya kelas X SMKN 3 Balikpapan.